Republic of Mozambique : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Mozambique. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that growth in Mozambique decelerated in 2016 to 3.8 percent (from 6.6 percent in 2015). The latest data show that the economy grew by 3.7 percent in 2017, driven by a recovery in agriculture and mining activity. A tight monetary stance, coupled with exchange rate appreciation, led to a steep fall in inflation to 6.3 percent (year-over-year) in January 2018, from a peak of 26 percent in November 2016. The outlook remains challenging. Absent further policy action, real GDP growth is expected to further decline over time while inflation would remain at current levels. The fiscal deficit would expand, leading to further accumulation of public debt and crowding out of the private sector.